Electricity in Africa the politics of transformation in Uganda - Gore, Christopher D. (Suffolk James Currey, 2017)
No country has managed to develop beyond a subsistence economy without ensuring at least minimum access to electricity for the majority of its population. Yet many sub-Saharan African countries struggle to meet demand. Why is this, and what can be done to reduce energy poverty and further Africa's development? Examining the politics and processes surrounding electricity infrastructure, provision and reform, the author provides an overview of historical and contemporary debates about access in the sub-continent, and explores the shifting role and influence of national governments and of multilateral agencies in energy reform decisions. He describes a challenging political environment for electricity supply, with African governments becoming increasingly frustrated with the rules and the processes of multilateral donors. Civil society also began to question reform choices, and governments in turn looked to new development partners, such as China, to chart a fresh path of energy transformation.
Includes bibliography and index
Keywords: Electrification -- Uganda; Electrification -- Social aspects -- Uganda; Electrification -- Economic aspects -- Uganda; Economic development -- Uganda